Boxing up death: The use of symbolic-material devices to address gestational and perinatal mourning in hospitals and families in Catalonia (Spain). - Fernández-Mostaza, María Esther; Muñoz-Henríquez, Wilson (Death Studies, 2025)
One of the strategies used by Spanish hospitals to address gestational and perinatal mourning is the "memory box." This box contains various elements that refer to the child who has died and seeks to help parents to move through the mourning process. This secular strategy has its historical roots in a popular ritual practice that has fallen into disuse called the "velorio del angelito" (the angel's wake). The purpose of this article is to analyze the role that the memory box plays in addressing mourning associated with perinatal or gestational death for affected families, highlighting how it aligns with and represents a departure from the angel's wake. Using a qualitative methodology that includes the analysis of hospital protocols-guidelines, interviews with key informants and a literature review, the authors demonstrate the similarities and differences that each one of these practices configures at the symbolic, material and social levels.